Processing reflexives in the second language: Evidence from eye tracking - Özturhan, Münir. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This thesis examines how Turkish learners of English process English reflexives (himself/herself). Two eye tracking experiments and a pen-and-paper antecedent identification task were employed to test whether Turkish learners of English were constrained by syntactic requirements associated with English reflexives, or other types of information such as discourse prominence or linear proximity influenced their antecedent retrieval behavior for the reflexives. The experimental materials in the two eye tracking experiments were adapted from Sturt (2003) and the materials in the antecedent identification task were largely based on those. Data were collected from 95 advanced learners of English. The results indicated that Turkish learners of English used structural constraints associated with the binding of English reflexives, but they were slower in their use of structural information compared to the native speakers in Sturt’s (2003) study. The use of structural information by Turkish learners of English was evident only in the eye tracking measures reflecting later stages of processing. There was no sign of use of non-structural cues such as discourse prominence and linear proximity in the eye tracking experiments, but their ultimate interpretations in the antecedent identification task were influenced by discourse-related information (although they chose the local noun as the antecedent for the reflexive > 79% of the time). The findings contradict the assumption that non native speakers rely more on non-structural cues (discourse prominence or linear proximity) than structural cues (syntactic constraints governing the binding of reflexives) during real-time sentence processing (Clahsen & Felser, 2006).
Keywords: Second language acquisition -- Turkey.; English language -- Reflexives.